Adherence to Taking Medication in Patients with Hypertension with Self Care Theory - Nurbadriyah, Wiwit Dwi; Fikriana, , Riza Fikriana; Novita, Zulfia (International Conference on Sustainable Health Promotion, 2021)
Hypertension is a degenerative disease that can affect anyone. Serious complications can occur in people with hypertension so that it needs to be handled quickly and appropriately, namely by taking medication. Therefore, adherence to medication is necessary in controlling blood pressure and preventing complications. The purpose of this study was to analyze medication adherence in patients with hypertension in Tegalsari Village, Kepanjen District.The design of this study used Analytical Observation with the Cross-Sectional method. The sample used is 92 people using Non Probability Sampling with Purposive Sampling technique. The process of collecting data using a questionnaire, then processing the data and continuing with linear regression statistical tests using the help of a computer program. The results of the Linear Regression test showed that the most influential variable on medication adherence was the attitude variable with a p-value <0.001.Based on these results, it is known that attitude is one of the most influential factors in medication adherence for patients with hypertension, so it is necessary to increase medication adherence for patients in their health behavior to prevent an increase in blood pressure and prevent complications.